2023
DOI: 10.3390/v15020360
|View full text |Cite
|
Sign up to set email alerts
|

SKI-1/S1P Facilitates SARS-CoV-2 Spike Induced Cell-to-Cell Fusion via Activation of SREBP-2 and Metalloproteases, Whereas PCSK9 Enhances the Degradation of ACE2

Abstract: Proprotein convertases activate various envelope glycoproteins and participate in cellular entry of many viruses. We recently showed that the convertase furin is critical for the infectivity of SARS-CoV-2, which requires cleavage of its spike protein (S) at two sites: S1/S2 and S2′. This study investigates the implication of the two cholesterol-regulating convertases SKI-1 and PCSK9 in SARS-CoV-2 entry. The assays used were cell-to-cell fusion in HeLa cells and pseudoparticle entry into Calu-3 cells. SKI-1 inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…Modeling at the molecular level indicated that ACE2 binds to the Pro/Catalytic domains of mature PCSK9. Thus, SARS-CoV-2 entrance can be modulated by the cholesterol-regulating convertases PCSK9 and SKI-1 via two distinct mechanisms [ 52 ]. Plasma PCSK9 levels were significantly elevated in our 156 patients with systemic inflammatory response syndrome (SIRS) or sepsis compared to the 68 healthy controls, according to the last studies.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 (Pcsk9) In Vir...mentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling at the molecular level indicated that ACE2 binds to the Pro/Catalytic domains of mature PCSK9. Thus, SARS-CoV-2 entrance can be modulated by the cholesterol-regulating convertases PCSK9 and SKI-1 via two distinct mechanisms [ 52 ]. Plasma PCSK9 levels were significantly elevated in our 156 patients with systemic inflammatory response syndrome (SIRS) or sepsis compared to the 68 healthy controls, according to the last studies.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 (Pcsk9) In Vir...mentioning
confidence: 99%
“…Necessary for the transportation of the PCSK9-LDLR complex to endosomes/lysosomes for degradation is the CHRD domain of PCSK9, particularly its M2 module. Surprisingly, the catalytic and/or prodomain of PCSK9 appear to be the critical domains for PCSK9 activity on ACE2, not the CHRD; this distinguishes ACE2 as a unique and novel PCSK9 target, quite distinct from the LDLR and MHC-I, which may partially explain this observation [ 52 ] …”
Section: Proprotein Convertase Subtilisin/kexin Type 9 (Pcsk9) In Vir...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential mechanism might BE related to the effect of PCSK9 on angiotensin-converting enzyme 2 (ACE2) entry receptors in COVID-19 [8]. Likewise, it has been reported that ACE2 suppresses abdominal sepsis and severe acute lung injury [9].…”
Section: Putative Mechanisms Of Pcsk9-induced Inflammation In Sepsismentioning
confidence: 99%
“…Furthermore, membrane cholesterol accelerates the formation of oligomeric S protein structures that enhance S2 activity ( Meher et al, 2023 ) ( Fig 1 ). Host site-1 protease (S1P)–mediated activation of sterol regulatory element–binding protein 2 (SREBP2), the major transcription factor that controls cholesterol homeostatsis, increased SARS-CoV-2 fusion with the cell membrane due to enhanced S2 processing in a HeLa (human cervical carcinoma) cell model ( Essalmani et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%